Bulky extramedullary plasmacytomata: rare mode of relapse in myelomatosis. Issue 3 (March 1989) - Davies, S V; Jones, B; Starkie, C M; Murray, J A
Abstract : In two cases of myelomatosis relapse was accompanied by the development of bulky extramedullary plasma cell tumours, which created serious management problems. In both cases the histology was of a poorly differentiated plasmacytoid tumour with frequent mitoses. In one case paraprotein had completely disappeared from the serum and urine after six months' treatment with melphalan alone but did not correlate with improved survival. It is concluded that extramedullary spread of myelomatosis in the form of bulky tumour deposits is a rare and ominous mode of tumour progression or relapse. Rises in serum and urinary paraprotein concentrations are not the inevitable signs of relapse.